Pengaruh Brand Awareness, Brand Association, dan Brand Loyalty Terhadap Pembelian Kembali Produk Bumbu Merek MyTaste - Razki, Muhammad Hanizar; Yulia, Iis Anisa; Fitrianti, Dewi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
This study aims to determine the effect of Brand Awareness, Brand Association, and Brand Loyalty on Repurchase of Mytaste Brand Seasoning Products. The sample used in this study were consumers who had purchased Mytaste seasoning products in Jabodetabek and obtained 130 respondents. The data analysis technique used multiple linear regression method. The results of the study showed that Brand Awareness, and Brand Loyalty partially influenced Repurchase, while Brand Association partially did not influence Repurchase. The results of the F test showed that simultaneously Brand Awareness, Brand Association and Brand Loyalty influenced Repurchase.